Modern ontology: reflection on the continuity of cyberspace and virtual reality: Ontología moderna: reflexión sobre la continuidad del ciberespacio y realidad virtual - Getman, Anatolii P.; Danilyan, Oleg G.; Dzeban, Aleksander P.; Kalynovskyi, Yurii Yu. (Revista de Filosofía, 2022)
The article demonstrates that information and communication technologies, which are actively implemented in modern life, have no analogues in the past. Reality, characterized by the concept of “cyberspace”, has become one of the main factors of socio-cultural reality, a special living environment with which all spheres of public life are connected − economic, social, political, spiritual. Modernity is characterized by the emergence of electronic virtual reality, which significantly changes the language, bringing in new elements of communication. Today, the Internet in some way is a global information space that unites all existing telecommunications and information networks. It is stated that the formation of global information networks has become a direct consequence of computer technology, so the global information space is primarily cybernetic (computer) in nature. The question is raised about the spatial and temporal characteristics of virtual reality and their ontological substantiation, because cyberspace presupposes the existence of a certain world, characterized by the length and metrics represented in consciousness. The thesis about the sociality of cyberspace is substantiated. It is shown that cyberspace is artificially maintained and developed by real space, so it is concluded that it is impossible and inexpedient to study it as an independent phenomenon.